Simulations show potential for reduced emissions and carbon stocks increase in boreal forests under ecosystem management. Issue 6 (December 2012) - Boisvenue, C; Bergeron, Y; Bernier, P; Peng, C
Background: Forests have become a focal point of climate change mitigation and adaptation, and of tradable credit systems, due to their carbon storage potential. But are the objectives evolving from climate-responsible stewardship and environmental certification conflicting?Results: We present modeled evidence showing that ecosystem management and minimizing carbon emissions are not mutually exclusive in boreal forests.Conclusion: Management decisions have substantial implications for forest carbon maintenance, but carbon sequestered outside the system or emission savings from product substitution are also important. A careful accounting will be necessary to properly evaluate ecosystem services trade-offs for forest management. Of further concern is the projected reduction in fire cycle lengths potentially reducing the carbon sequestered in the boreal landscape.